Staghorn stone and squamous cell carcinoma of the renal pelvis: a clinical case and literature review - V. K. Dzitiev; N. I. Sorokin; V. E. Sinitsyn; O. Yu. Nesterova; N. V. Danilova; E. M. Badmaeva; A. A. Strigunov; D. D. Tsurskaya; A. A. Kamalov (Вестник урологии, 2023)
Squamous cell carcinoma of the renal pelvis is a rare neoplasm. The incidence does not exceed 1% of all neoplasms of this localization. In the general population, up to 90% of all neoplasms of the renal pelvis are represented by urothelial carcinoma, while from 0.7% to 7.0% of cases are squamous cell carcinoma. Stones of the renal collecting system are found in 14 – 50% of patients with squamous cell carcinoma of the pelvis. As a possible etiopathogenetic mechanism, chronic inflammation on the background of a stone is considered, leading to squamous urothelial metaplasia with subsequent keratinization and malignization. Clinical manifestation of squamous cell carcinoma of the renal pelvis is nonspecific and is primarily associated with manifestations of urolithiasis. Squamous cell carcinoma of the renal pelvis is characterised by high aggressiveness, insensitivity to chemotherapy and radiation therapy, and consequently an unfavourable prognosis. The survival rate of most patients is less than one year from the diagnosis, while the 5-year survival rate does not exceed 10%. We present our own clinical case of a patient with a staghorn stone and squamous cell carcinoma of the renal pelvis.